A New Data Set On Competition In National Banking Markets. Issue 2 (6th April 2015) - Clerides, Sofronis; Delis, Manthos D.; Kokas, Sotirios
Abstract : We estimate the degree of competition in the banking sectors of 148 countries over the period 1997–2010 using three methods: the Lerner index, the adjusted Lerner index, and the profit elasticity. Marginal cost estimates required for all methods are obtained using a flexible semi‐parametric methodology. All three indices show that competitive conditions in banking deteriorated during the period 1997–2006, improved until 2008, and deteriorated again thereafter. Levels of competition differ across regions and income groups, but there is gradual convergence over time. Banking system is less competitive in sub‐Saharan Africa and low income countries and more competitive in Europe and Central and South Asia and OECD countries.